Bulleyaconitine A Exerts Antianxiety and Antivisceral Hypersensitivity Effects - Huang, Sheng-Nan; Yang, BeiBei; Ma, Le; Huang, Lan-Ting; Ju, Pei-Jun; Wei, Jinbao; Ali, Usman; Wang, Yong-Xiang; Chen, Jinghong (Frontiers in Pharmacology, 2020)
Visceral pain is one of the leading causes for abdominal pain in gastroenterological diseases and is still hard to treat effectively. Bulleyaconitine A (BAA) is an aconitine analogue and has been usedfor the treatment of pain. Our previous work suggested that BAA exerted analgesic effects on neuropathic pain through stimulating the expression of dynorphin A in spinal microglia. Here we investigated the inhibitory effect of BAA on visceral pain and examined whether the expression of dynorphin A in spinal microglia was responsible for its effects. We found that BAA produced significant anti-visceral pain effect induced by acetic acid through stimulating dynorphin A expression in spinal microglia. In addition, anxiety and chronic visceral pain are highly prevalent comorbid conditions in clinical research, which is still a problem to be solved. We also aimed to evaluate the effect of BAA on anxiety. A comorbidity model with characteristics of both chronic visceral pain and anxiety was developed by colorectal injection of 2,4,6-trinitrobenzene sulfonic acid and the induction of Heterotypic Intermittent Chronic Stress protocol. In comorbid animals, BAA exerted great anti-anxiety effects. Meanwhile, the anti-anxiety mechanism of BAA was different with the anti-visceral pain mechanism of BAA. In conclusion, our study demonstrated, for the first time, that BAA exerted marked anti-visceral pain and anti-anxiety effects, which expands the analgesic spectrum and clinical application of BAA. Also it provides further guidance for the clinical use of BAA.